Calliphoridae (Diptera) of the coastline of Buenos Aires, Argentina : species composition, numerical trends, and bait's preferences - Mulieri, Pablo R. (2006)
Fil: Mulieri, Pablo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Vectores; Argentina.